2010 Joint Rail Conference, Volume 1 2010
DOI: 10.1115/jrc2010-36146
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Asphalt/Bituminous Layers and Coatings in Railway Trackbeds: A Compendium of International Applications

Abstract: During the past thirty years the use of a layer(s) of hot-mix asphalt pavement within railway track structures has steadily increased until it is becoming a common consideration or practice for specific conditions and areas in several countries throughout the world. This practice augments, and for certain designs replace, the traditional granular support materials. It is considered to be a premium trackbed design. The primary documented benefits are to provide additional support to improve load distributing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 4 publications
0
24
0
2
Order By: Relevance
“…According to [17], the asphalt content should be up to 0.5% greater than that considered for pavement application with air voids of 1-3%. A comparative evaluation of different structures for the trackbed, which demonstrated the combination of asphalt trackbed and subballast layer for a higher service life, based on KENTRACK software was introduced by [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to [17], the asphalt content should be up to 0.5% greater than that considered for pavement application with air voids of 1-3%. A comparative evaluation of different structures for the trackbed, which demonstrated the combination of asphalt trackbed and subballast layer for a higher service life, based on KENTRACK software was introduced by [18].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it has also been successfully applied in railway structures. Worldwide experience has shown that the use of asphalt materials can offer a good alternative in modern railway construction [8,9]. At present, the application of asphalt layers in railway track systems can be classified into three categories, namely asphalt sub-ballast layer in the ballast railway track, asphalt supporting layer in the ballastless railway track, and the asphalt waterproofing layer in the slab track.…”
Section: Introductionmentioning
confidence: 99%
“…For its application as sub-ballast, however, some authors recommend increasing the content of bitumen by 0.5% in comparison with that considered as optimum for highway applications in mixtures with air-voids content of 1-3% (10).…”
Section: Introductionmentioning
confidence: 99%